Demarcation and the Scientistic Fallacy - Peterson, Gregory R. (Zygon, 2003)
Abstract. For many theologians and philosophers, scientism is among the greatest of intellectual sins. In its most commonly cited form, scientism consists in claiming that science is the only source of real knowledge and, therefore, that what science does not discover does not exist. Because the charge of scientism is frequently levied, it is important to be clear about what exactly is being claimed in its name. I argue that scientism can best be understood as a fallacy, specifically as a kind of category mistake. Being clear about this requires an examination of the relationship of scientism to the question of demarcation between science and nonscience, a question that has potential implications for theology.